2022
DOI: 10.1002/brb3.2834
|View full text |Cite
|
Sign up to set email alerts
|

Working status and risk of Alzheimer's disease: A Mendelian randomization study

Abstract: Background: Alzheimer's disease (AD) has become a common illness affecting the elderly, adding to society's social and financial burden. We used two-sample Mendelian randomization (MR) in this study to determine the association between working status and AD. Methods:We performed a two-sample MR analysis. The genetic associations were derived from the UK Biobank (n = 263,615) and the International Genomics of Alzheimer's Project (n = 63,926). Inverse variance weighted (IVW), MR-Egger, and weighted median were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Work‐related factors have been recognized to influence the development of neurodegenerative diseases including dementia, Alzheimer's disease, and ALS. It has been shown that manual work is positively associated with the risk of developing Alzheimer's disease (Zhao et al., 2023 ). The risk of all‐cause dementia is increased in the shift‐working population (Liao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work‐related factors have been recognized to influence the development of neurodegenerative diseases including dementia, Alzheimer's disease, and ALS. It has been shown that manual work is positively associated with the risk of developing Alzheimer's disease (Zhao et al., 2023 ). The risk of all‐cause dementia is increased in the shift‐working population (Liao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…MR methods are also known as natural RCTs because the process of assigning alleles from parent to offspring is similar to random grouping in RCT (Davies et al., 2018 ), and thus, MR methods can overcome some of the limitations in observational studies and minimize confounding factors and reverse causality (Davey Smith & Hemani, 2014 ). The effect of work‐related factors on some neurodegenerative diseases such as Alzheimer's disease has been demonstrated by MR (Zhao et al., 2023 ), but there is still a lack of MR studies of work‐related factors on ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant investments in neurological research, the exact molecular mechanism of AD pathogenesis is still not fully elucidated [4,5] . AD, therefore, would develop into a crucial threat to the public health and cause huge financial burden to the social welfare system, if we cannot innovate AD diagnostic and therapeutic paradigms in time [6,7] …”
Section: Introductionmentioning
confidence: 99%
“…[4,5] AD, therefore, would develop into a crucial threat to the public health and cause huge financial burden to the social welfare system, if we cannot innovate AD diagnostic and therapeutic paradigms in time. [6,7] Generally, the clinical manifestations of AD mainly include memory loss, language impairment, progressive mental decline, personality and behavior changes. [8] Currently, clinical examination and neuropsychological tests are still the general standard for definite diagnosis of AD.…”
Section: Introductionmentioning
confidence: 99%